First record of the genus Alainites Waltz & McCafferty, 1994 (Ephemeroptera, Baetidae) from India with the description of a new species from the North-western Himalayas - Sohil, Asha; Srinivasan, Pandiarajan; Sivaruban, T.; Barathy, S.; Gattolliat, Jean-Luc; Sharma, Neeraj (European Journal of Taxonomy, 2023)
A new species Alainites neeru sp. nov. is described based on larvae collected from a hill stream in Jammu and Kashmir, India. It is the first report of the genus Alainites Waltz & McCafferty, 1994 from India. The new species is closely related to the Palearctic species A. muticus (Linnaeus, 1758), but can be distinguished from the latter by the length of the maxillary palp, the reduced number of spine-like setae on the margin between the prostheca and mola of the right mandible, the reduced tracheation in the tergalii, and by a reduced number of spines on the prolongation of the paraproct. With this record, the genus Alainites encompasses a total of twenty-two species.